2021
DOI: 10.1111/cdev.13537
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Auditory Time Perception in Children With Motor Difficulties

Abstract: Accurate time perception is crucial for hearing (speech, music) and action (walking, catching). Motor brain regions are recruited during auditory time perception. Therefore, the hypothesis was tested that children (age 6-7) at risk for developmental coordination disorder (rDCD), a neurodevelopmental disorder involving motor difficulties, would show nonmotor auditory time perception deficits. Psychophysical tasks confirmed that children with rDCD have poorer duration and rhythm perception than typically develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 100 publications
(169 reference statements)
1
19
1
Order By: Relevance
“…Chang et al . [102] hypothesized that children with DCD would show deficits in both auditory duration perception and auditory rhythm perception given evidence that the auditory system connects with the motor system to accomplish time perception. Using psychophysical methods, they found that, compared to TD children, those with DCD had poorer discrimination thresholds for detecting changes in the duration of single time intervals, and detecting the presence of non-isochrony in an otherwise isochronous tone sequence, while their pitch discrimination thresholds were relatively unaffected.…”
Section: Developmental Coordination Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al . [102] hypothesized that children with DCD would show deficits in both auditory duration perception and auditory rhythm perception given evidence that the auditory system connects with the motor system to accomplish time perception. Using psychophysical methods, they found that, compared to TD children, those with DCD had poorer discrimination thresholds for detecting changes in the duration of single time intervals, and detecting the presence of non-isochrony in an otherwise isochronous tone sequence, while their pitch discrimination thresholds were relatively unaffected.…”
Section: Developmental Coordination Disordermentioning
confidence: 99%
“…While the auditory and motor systems are intimately connected, little research has investigated auditory time and rhythm perception in DCD in the absence of a motor task. Chang et al [102] hypothesized that children with DCD royalsocietypublishing.org/journal/rstb Phil. Trans.…”
Section: Developmental Coordination Disordermentioning
confidence: 99%
“…Impaired timing mechanisms also often co-occur in developmental disorders that are frequently characterized by speech and language impairments (see Lense et al, in press, for a review). Timing impairments have been observed, for example, in Autism Spectrum Disorder (Duffield et al, 2013; Green et al, 2009; Hardy & LaGasse, 2013; Isaksson et al, 2018; Morimoto et al, 2018; Mostofsky et al, 2009; Rinehart et al, 2001; Tryfon et al, 2017), Attention Deficit Hyperactivity Disorder (Hove et al, 2017; Noreika et al, 2013; Puyjarinet et al, 2017; Rubia et al, 1999; Shapiro & Huang-Pollock, 2019; Slater & Tate, 2018; Valera et al, 2010; Zelaznik et al, 2012), and Developmental Coordination Disorder (DCD; Chang et al, 2021; Rosenblum & Regev, 2013; Trainor et al, 2018). In the adult-focused brain pathology literature, comorbid timing deficits have also been observed linked to basal ganglia dysfunction/impairments, such as in Parkinson’s disease and patients with basal ganglia lesions (Kotz et al, 2005; Kotz & Gunter, 2015).…”
Section: Predictions and Future Directions Of The Prism Frameworkmentioning
confidence: 99%
“…In the cognitive domain, early rhythm perception abilities have been linked to grammar abilities (Gordon et al, 2015). Music trainingspecifically, rhythmic trainingis proposed to be a potentially viable Children and Groove 4 intervention for children with developmental disorders (Chang et al, 2021;Lense & Camarata, 2020;Wiens & Gordon, 2018). Proposed interventions often focus on strengthening time perception mechanisms via encouraging musical movements.…”
Section: Musical Groove Shapes Children's Free Dancingmentioning
confidence: 99%
“…Identifying types of music that facilitate temporally correspondent movements and ultimately, synchronization, has important implications on rhythmic intervention programs. For example, training children to move in synchrony to musical rhythms is proposed as one pathway to remediate language skills, coordination skills, and social skills for children with deficits (Chang et al, 2021;Lense & Camarata, 2020;Wiens & Gordon, 2018). More generally, moving synchronously to music with others can help toddlers and young children forge social connections with their movement partners (Cirelli et al, 2018).…”
Section: Children and Groove 17mentioning
confidence: 99%